2009
DOI: 10.1007/978-3-642-04138-9_23
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency Injection Attack on Ring-Oscillator-Based True Random Number Generators

Abstract: Abstract. We have devised a frequency injection attack which is able to destroy the source of entropy in ring-oscillator-based true random number generators (TRNGs). A TRNG will lock to frequencies injected into the power supply, eliminating the source of random jitter on which it relies. We are able to reduce the keyspace of a secure microcontroller based on a TRNG from 2 64 to 3300, and successfully attack a 2004 EMV ('Chip and PIN') payment card. We outline a realistic covert attack on the EMV payment syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 12 publications
0
103
0
1
Order By: Relevance
“…Markettos and Moore [7] explored how otherwise secure true random number generators could be manipulated to produce more deterministic output, and how to exploit a weak RNG in an EMV transaction. But this paper is the first work to show that poor random number generators exist in the wild, that they have been implicated in fraud, how they can be exploited, and the protocol flaws in the EMV specification that make this so hard to counter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Markettos and Moore [7] explored how otherwise secure true random number generators could be manipulated to produce more deterministic output, and how to exploit a weak RNG in an EMV transaction. But this paper is the first work to show that poor random number generators exist in the wild, that they have been implicated in fraud, how they can be exploited, and the protocol flaws in the EMV specification that make this so hard to counter.…”
Section: Discussionmentioning
confidence: 99%
“…Even the suggested construction (hash or exclusive-or of previous ARQCs, transaction counter and time) would not be adequate if the ATM is rebooted and both the time and transaction counter are predictable. 1) UN data collection: Markettos and Moore [7] first showed that a pre-play attack was possible against EMV if the attacker could sabotage the RNG. However, before our work, there was no empiral work on the quality of the RNGs used by actual ATMs or POS terminals.…”
Section: B Pre-play Attacks Based On a Weak Rngmentioning
confidence: 99%
“…Controlled variation in power supply or temperature fluctuations are used to attack the TRNG devices and control the randomness of the bits generated. In [11], R. Santoro et al have demonstrated an attack on ring oscillator based TRNG used in a smart card by introducing noise on the power supply through electromagnetic injection. Such an attack reduced the entropy of the TRNG and hence made the smart card unsafe for use.…”
Section: Effect Of Variation On Biasmentioning
confidence: 99%
“…For example, in [4] Markettos and Moore could manipulate "random" numbers generated in a secure commercial processor by injecting a periodic signal to its power supply. In [5], Bayon et al could manipulate numbers generated by a set of 50 ring oscillators even to a bigger extent by using strong electromagnetic fields.…”
Section: Introductionmentioning
confidence: 99%